Isolation and characterization of polyketide drug molecule from Streptomyces species with antimicrobial activity against clinical pathogens - Mohammed A. Almalki (Elsevier, 2020)
Background: Natural products derived from marine microbes have more potential toward to treatment of various diseases. Among the microbes, the secondary metabolites recovered from the marine actinomycetes were more added values. Objective: A promising antimicrobial metabolite producing filamentous actinomycete SCA-7 recovered from Alkhobar marine region was investigated for its potential to inhibit Gram positive Enterococcus sp. In addition to the chemical characterization, the polyketide gene cluster of the actinomycete SCA-7 was sequenced. Results: Among the 8 actinomycetes isolated from the marine sample, the isolate SCA-7 produced significant antimicrobial activity against Enterococcus sp. The biochemical, physiological and morphological characteristics and fermentation assimilation pattern confirmed that the isolate belonged to the genus Streptomyces. The 16S rRNA gene amplification and sequencing results showed 99% sequence similarity to Streptomyces felleus. The antimicrobial activity of the crude ethyl acetate extract was performed by disc diffusion method. The spectral characterization was done by 13C NMR and 1H NMR. The compound was polyketide in nature. The Minimum Inhibitory Concentration (MIC) of the polyketide compound against Enterococcus sp. was 25 μg/mL. Among the agro-industrial waste materials, wheat bran showed increased secondary metabolite production. Antibacterial activity was found to be high when the isolate SCA-7 was grown in wheat bran substrate and maximum zone of inhibition (22 mm) was recorded in it. Among the carbon and nitrogen sources, lactose enhanced the production of secondary metabolites and the zone of inhibition against Enterococcus sp. was 25 mm. The amplification and sequencing of the ketoacyl synthase gene clearly indicated that it was type I polyketide synthase (PKS) gene of Streptomyces species. Conclusion: Overall, the therapeutic drug molecule isolated from the marine Streptomyces species might be used for the treatment of disease causing microbial clinical pathogen. Keywords: Streptomyces sp., Antimicrobial activity, Minimum inhibitory concentration, Ketoacyl synthase gene